POTENSI DAN REALISASI DANA ZAKAT INDONESIA - Clarashinta Canggih; Khusnul Fikriyah; Ach. Yasin (Universitas Negeri Surabaya, 2017)
This paper aims to find out illustration and estimation of zakat potency as well as the amount of zakat collection in Indonesia. Furthermore, it aims to outline the diversity between potency and realization of zakat. It used quantitative descriptive approach through secondary data collection from several sources. The result shows both potency and realization of zakat collection in Indonesia were increasing during 2011-2015. However, the amount of zakat potency surpasses the amount of zakat realization with wide gap.It shows that the average amount of zakat collection on 2011-2015 is less than 1% compare to its potency. One of the possible reason is most of Indonesian prefer to distribute their zakat directly to the muzakki, hence it is unrecorded.